Sex differences in motor learning flexibility are accompanied by sex differences in mushroom spine pruning of the mouse primary motor cortex during adolescence - Tekin, Michael; Shen, Hui; Smith, Sheryl S. (Frontiers in Neuroscience, 2024)
Background Although males excel at motor tasks requiring strength, females exhibit greater motor learning flexibility. Cognitive flexibility is associated with low baseline mushroom spine densities achieved by pruning which can be triggered by α4βδ GABAA receptors (GABARs); defective synaptic pruning impairs this process. Methods We investigated sex differences in adolescent pruning of mushroom spine pruning of layer 5 pyramidal cells of primary motor cortex (L5M1), a site essential for motor learning, using microscopic evaluation of Golgi stained sections. We assessed α4GABAR expression using immunohistochemical and electrophysiological techniques (whole cell patch clamp responses to 100 nM gaboxadol, selective for α4βδ GABARs). We then compared performance of groups with different post-pubertal mushroom spine densities on motor learning (constant speed) and learning flexibility (accelerating speed following constant speed) rotarod tasks. Results Mushroom spines in proximal L5M1 of female mice decreased >60% from PND35 (puberty onset) to PND56 (Pubertal: 2.23 ± 0.21 spines/10 μm; post-pubertal: 0.81 ± 0.14 spines/10 μm, P < 0.001); male mushroom spine density was unchanged. This was due to greater α4βδ GABAR expression in the female (P < 0.0001) because α4 -/- mice did not exhibit mushroom spine pruning. Although motor learning was similar for all groups, only female wild-type mice (low mushroom spine density) learned the accelerating rotarod task after the constant speed task (P = 0.006), a measure of motor learning flexibility. Conclusions These results suggest that optimal motor learning flexibility of female mice is associated with low baseline levels of post-pubertal mushroom spine density in L5M1 compared to male and female α4 -/- mice.